Potential of Water Hyacinth (Eichornia crassipes) Activated Carbon as Adsorbent for Heavy Metal Pb in Wastewater of Hapsah Hospital Bone Regency - S. Kasim; I. Zahrawani (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2026)
The water hyacinth plant is one of the plants that has potential as a bio-adsorbent. Water hyacinth has the ability to absorb heavy metals such as Pb because it has a high cellulose content of 60%, hemicellulose 8%, and lignin 17%, and has been proven effective in dealing with environmental pollution. This study aims to analyze the potential of water hyacinth as an adsorbent of lead metal ions (Pb), determine the initial and final concentration of wastewater that has been adsorbed using water hyacinth adsorbent of lead metal ions (Pb) in the wastewater of Rumah Sakit Hapsah Bone Regency, and characterize water hyacinth activated carbon before and after adsorption. The process of making water hyacinth activated carbon, characterization of water hyacinth activated carbon, analysis of lead metal (Pb) levels in wastewater using SSA, and application of water hyacinth activated carbon to wastewater. The results showed that the initial level of lead metal ions (Pb) in the wastewater of Hapsah Hospital, Bone Regency was 0.68 mg/L, and water hyacinth activated carbon showed optimal adsorption ability at a contact time of 20 minutes and mass of 2 grams. Based on the results of the research that has been done, it can be concluded that the activated carbon produced from water hyacinth has the best quality.